Um novo aplicativo educacional para o estudo de juros simples e compostos. - BRITO, Anderson da Silva (Universidade Federal do Tocantins, 2023)
In view of the increasing technological advances, especially with regard to the mobile technology, and specifically the use of the phone as a resource in school education, the question defined guideline for this work: how to develop an application that can be used on mobile for the study of simple and compound interest? This work aimed to develop an educational application through the platform MIT App Inventor who can be useful in the study of financial mathematics topics, related to simple and compound interest. To this end, initially were carried out searches for references on mobile technology, use of ICTs in education and the importance of financial mathematics to the formation of the student/citizen. Later, for creating an application for mobile phones with Android operating system, in which we opted for the use of the platform MIT App Inventor, with the aid of tutorials available, on its Web site. Given the importance of the subject, it is essential to the development of new applications that can serve as resources to teachers in the teaching of mathematics and that may encourage students to develop skills and abilities in order to meet the different demands of knowledge needed for decision making regarding the use of the money conscious. Anyway, as a result of this work was to create an educational application for mobile devices that can complement the teaching and enhance learning in interactive, dynamic and constructive.